Restitution Through Equity-Focused Mentoring: A Solution to Diversify the Physician Workforce - Valencia P. Walker; Valencia P. Walker; Dominique R. Williams; Dominique R. Williams (Frontiers in Public Health, 2022)
Minoritized and marginalized physicians who identify as Black, Latino/a/x and Native American (BLNA) remain unacceptably underrepresented in medicine. Multiple studies provide a compelling argument for prioritizing racial/ethnic diversification of the physician workforce to improve racial/ethnic physician-patient concordance and assist in achieving more equitable health outcomes. Despite a growing awareness for the tangible benefits of a diversified physician workforce, the number of physicians from minoritized and marginalized groups remains relatively stagnant or worsening in certain demographics. The 5:1 ratio of Black students and trainees to Black faculty exemplifies and exacerbates the increased risk for harmful isolation particularly experienced by many BLNA mentees. They too need and deserve the benefits produced by concordant racial/ethnic faculty mentoring and support. However, these demands on time, resources and bandwidth can lead to negative consequences for BLNA faculty engaged in these efforts by contributing to their emotional, mental and physical exhaustion. Given the perpetual paucity of BLNA physicians in academic medicine, immediate interventions to prevent attrition of BLNA faculty, trainees and students journeying along the physician career pathway are urgently needed. Requiring the implementation of mentoring programs explicitly focused on increasing the number of physicians from groups underrepresented in medicine must happen at every point of the education and training process.